Cellulase Production by Trichosporon laibachii - Giese, Ellen C.; Dussán, Kelly J.; Pierozzi, Maurício; Chandel, Anuj K.; Pagnocca, Fernando C.; da Silva, Silvio Silvério (Orbital: The Electronic Journal of Chemistry, 2017)
The ability of twenty-three yeast strains isolated from decayed wood and the fungus garden of attine ants to produce hemi- and cellulolytic hydrolases in a chemically defined medium was screened. Xylanase, β-glucosidase and cellulase activities were found in yeasts strains in the genera Cryptococcus, Trichosporon, Debaryomyces and Pichia. Among the isolated microorganisms, two strains of Trichosporon laibachii MG270406-1A14 strain showed higher cellulase titers. Several biochemical and physiological parameters were investigated for optimum cellulase production under submerged fermentation. Enzyme induction was also examined using different carbon and nitrogen sources. Cellobiose and ammonium sulphate were found best carbon (C) and nitrogen (N) sources to enhance carboxymethylcellulase production. A 22- factorial design with center points was developed to optimize enzyme production, and data analysed by the response surface method. Maximal enzyme titres (0.3 U mL-1) occurred at initial pH 6.0, C/N ratio 9.0 and 5 days. DOI: http://dx.doi.org/10.17807/orbital.v9i4.1024